2015
DOI: 10.1177/1457496914568408
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular reconstruction with impaction bone grafting and cemented polyethylene socket in total hip revision arthroplasty

Abstract: Our results were inferior compared to some previous studies. Impaction bone grafting of acetabular defects in revision total hip arthroplasty may not always provide a reliable bone stock in long-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The graft should be prepared using large rongeurs or a bonemill, although the latter produces a smaller size bone chip. Our experience confirms previously published data 7 11 12) showing that larger bone chip sizes of around 8 mm produce increased stability for acetabular IBG; therefore–despite being time-consuming–we recommend hand-made bone chips using rongeurs ( Fig. 1 , 2 , 3 ).…”
Section: Technical Aspects Of Impaction Bone Graftingsupporting
confidence: 88%
“…The graft should be prepared using large rongeurs or a bonemill, although the latter produces a smaller size bone chip. Our experience confirms previously published data 7 11 12) showing that larger bone chip sizes of around 8 mm produce increased stability for acetabular IBG; therefore–despite being time-consuming–we recommend hand-made bone chips using rongeurs ( Fig. 1 , 2 , 3 ).…”
Section: Technical Aspects Of Impaction Bone Graftingsupporting
confidence: 88%
“…1,2 Over the previous decades, the incidence of revision and re-revision has risen because of an ageing population as well as an increasing occurrence of THA in young patients. 3 Periprosthetic hip fractures are increasingly frequent; their incidence is reported to be between 1% to 2.3% of primary implant and up to 7.8% in revision hip implants. 4 Periprosthetic fractures are complex injuries and most commonly affect an elderly cohort of patients with multiple co-morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Over the previous decades, the incidence of revision and re-revision has risen because of an ageing population as well as an increasing occurrence of THA in young patients. 3…”
Section: Introductionmentioning
confidence: 99%
“…However, other authors reported inferior results, both in major bone loss and without correlation with the type of defect. 27,28 The surgeon’s experience makes the difference in this demanding technique. Iwase reported favourable results only in cases of moderate bone loss with a maximum depth of 20 mm and without multiple segmental defects.…”
Section: Allograftsmentioning
confidence: 99%